A Chiral, Self-Catenating and Porous Metal-Organic Framework and its Post-Synthetic Metal Uptake - Jacobs, Tia; Clowes, Rob; Cooper, Andrew I.; Hardie, Michaele J. (Angewandte Chemie International Edition, 2012)
Free vacancies: A robust and porous metal–organic framework material with unique 4‐connected self‐catenating structure of {85⋅10} topology was synthesized. The structure features empty bipyridine metal‐chelating sites that can be doped with copper cations in a single‐crystal‐to‐single‐crystal post‐synthetic modification (see picture; scale bar 20 μm).